Entorno escolar y su influencia en el desarrollo de las habilidades blandas en los estudiantes de EGB de 5to grado de la Escuela Nicolas Vásconez del Recinto Cimarrón del Cantón Baba - Triviño Granados, María Fernanda (2025)
This research analyzes the influence of the school environment on the development of soft skills of 5th grade students of Basic General Education at the Nicolás Vásconez School in the Baba canton during the period 2024. The study is based on global research that points out a significant gap between the soft skills required in the world of work and those developed in traditional educational systems. In Ecuador, approximately 45% of public educational institutions have deficiencies in their school environments that limit the comprehensive development of students, a situation recognized in the Ten-Year Education Plan 2016-2025. The research uses a mixed approach, combining qualitative and quantitative methods, with a non-experimental field design. The study is carried out with a total population of 51 participants, made up of 46 5th grade students and 5 teachers from the institution. For data collection, techniques such as systematic observation, semi-structured interviews with teachers, and Likert-scale surveys for students will be implemented, using instruments designed to assess both the characteristics of the school environment and its impact on the development of soft skills. The expected results of this research seek to demonstrate the relationship between a positive school environment and the effective development of soft skills in students, particularly in aspects such as effective communication, teamwork, critical thinking, and problem solving. It is anticipated that the findings will provide concrete tools and strategies to optimize the school environment and strengthen the comprehensive development of students.